The Attitudes of Undergraduates toward the Use of Mobile Applications for Learning English - Rahman Nur, Dedi; Nur Hidayati, Ratri; Fajria, Astry; Widyaningsih, Nina (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Although extensive research has been conducted on the positive impact of Mobile Assisted Language Learning (MALL) on student learning, there have been few studies examining university students' attitudes toward the use of MALL for English learning. The study investigates the attitudes of university students toward MALL, focusing on the use of mobile applications to learn English. This study's participants are the English department at a private university in East Kalimantan. This study employs a questionnaire and a semi-structured interview for data collection. The findings from this analysis demonstrated that students had a favorable perception of the usefulness of MALL in various aspects of language learning. They perceived English mobile applications as beneficial for improving their language skills, enhancing work quality, and promoting motivation. These positive perceptions indicated that MALL had the potential to be an effective tool in supporting language learning among students